Performance Optimization of Gas Turbine Engine by Direct-Contact-Air-Washer - Elsaied Mohamed, Waiel Kamal (2009)
This research focuses on the performance enhancement of a gas turbine by cooling the compressor inlet air. The effects of ambient conditions i.e. temperature, pressure and relative humidity were investigated. An innovative approach for cooling the compressor inlet air by Direct-Contact Air-Washer is proposed. Heat and mass transfer model was developed to determine the effectiveness of the Air-Washer system. Subsequently, analytical and simulation model for prediction of the performance of a single-shaft commercial gas turbine from the component models was developed. The simulation model is based on matching technique, and mass and energy balance. Component performance maps were used to determine the steady state part-load operation of each component.